Want this question answered?
Be notified when an answer is posted
2(x+6)=2x+12. This is an example of the distributive property.
(3 - y + 2x)(3 + y - 2x)
(2x2+4xy-3)-(x2-2xy-4)Answer: x2+6x+1
(2x)(2y) is the exact same as (2)(x)(2)(y) since they are all multiplication, which can be rearranged in any order, so this is also the same as (2)(2)(x)(y), which is the same as (4)(x)(y), so in the end: (2x)(2y)=4xy
2x(a+3b)=2xa+6xb
6x2-2x
The GCF is 2x.
2x
10xy+x
4x2 - 4xy + y2 = (2x - y)2 so the length of the side of the square must be 2x-y.
2(x+6)=2x+12. This is an example of the distributive property.
(3 - y + 2x)(3 + y - 2x)
(2y)(2x - 3z)
4xy/0.25x = 16y
(2x2+4xy-3)-(x2-2xy-4)Answer: x2+6x+1
2x(4+8) = 2x(4) and 2x(8)
2x(3x-1) = 6x2-2x because of the distributive property.